A Known-Groups Validation of the Medical Symptom Validity Test and Analysis of the Genuine Memory Impairment Profile. (April 2022) - Resch, Zachary J.; Rhoads, Tasha; Ovsiew, Gabriel P.; Soble, Jason R.
This study cross-validated the Medical Symptom Validity Test (MSVT) in a mixed neuropsychiatric sample and examined its accuracy for identifying invalid neuropsychological performance using a known-groups design. Cross-sectional data from 129 clinical patients who completed the MSVT were examined. Validity groups were established using six, independent criterion performance validity tests, which yielded 98 patients in the valid group and 31 in the invalid group. All MSVT subtest scores were significantly lower in the invalid group (η p 2 =.22-.39). Using published cut-scores, sensitivities of 42% to 71% were found among the primary effort subtests, and 74% sensitivity/90% specificity was observed for the overall MSVT. Among this sample, the MSVT component validity scales produced areas under the curve of .78-.86, suggesting moderate classification accuracy. At optimal cut-scores, the MSVT primary effort validity scales demonstrated 55% to 71% sensitivity/91% to 93% specificity, with the Consistency subtest exhibiting the strongest psychometric properties. The MSVT exhibited relatively robust sensitivity and specificity, supporting its utility as a briefer freestanding performance validity test to its predecessor, the Word Memory Test. Finally, the Genuine Memory Impairment Profile appears promising for patients with Major Neurocognitive Disorder, but is cautioned against for those without significant functional decline in activities of daily living at this time.